The changing role of subjects connected with book history and publishing in the education of library specialists in Estonia - Aile Möldre (Information Research: An International Electronic Journal)
Gives an overview of the development of library education in Estonia since the beginning of teaching library science on the academic level in 1927 up to the present day. The author concentrates on studying the role and share of the courses that deal with book history and contemporary development of the book trade during different periods of time (the Soviet era, and after the restoration of independence in 1991). The last part of the article presents data on the evaluation of the usefulness and necessity of these subjects by public librarians and students of the Tallinn Pedagogical University.